2012
DOI: 10.2165/11593030-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Common Drug Review Recommendations

Abstract: This analysis documented an evidence-driven process that simultaneously weighted multiple factors. Clinical uncertainty and price considerations, but not economic results, had a strong impact on the recommendations. Insufficiency of clinical evidence may have resulted from the gap in evidence available at the time of product launch and the absence of demonstrated benefits to support innovative drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
(25 reference statements)
1
28
0
Order By: Relevance
“…Once the clinical hurdle had been passed, the agencies behaved differently. In Canada, cost-effectiveness did not influence the recommendation once clinical factors had been taken into account; rather, price remained as one of four statistically significant predictors of a recommendation 15. In the United Kingdom, Devlin et al16 found that cost-effectiveness explained 85% of NICE decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Once the clinical hurdle had been passed, the agencies behaved differently. In Canada, cost-effectiveness did not influence the recommendation once clinical factors had been taken into account; rather, price remained as one of four statistically significant predictors of a recommendation 15. In the United Kingdom, Devlin et al16 found that cost-effectiveness explained 85% of NICE decisions.…”
Section: Discussionmentioning
confidence: 99%
“…8 A CADTH official who was involved in setting up the CDR notes that at the time there were concerns with specific new drugs for multiple sclerosis and Alzheimer's disease, which were very expensive and where expert advice varied. 9 In a "myths versus facts" memo (Canadian Agency for Drugs and Technologies in Health 2011), CADTH responds by arguing there is little difference in cost between drugs that are recommended for listing compared to those that are not recommended; this has been supported by independent research (Rocchi et al 2012).…”
Section: Goals Of the Reformmentioning
confidence: 99%
“…This issue is mentioned in a variety 32 Interview with an expert committee member. 33 Interviews with an expert committee member, a former expert committee member and Torrance. of studies that note limited clinical data is an important predictor of a "do not list" recommendation (Clement et al 2009;Rocchi et al 2012). When it was designed, the CDR addressed shortcomings in drug assessment under the Canadian guidelines regarding limited uptake and the need for greater transparency.…”
Section: Analytical Comparisonmentioning
confidence: 99%
“…Biologics are particularly effective at controlling the symptoms of PsA and have been shown to delay disease progression in terms of joint erosion [1]. However, these treatments are expensive, and within resource constrained systems, their value for money has been assessed by health technology assessment (HTA) agencies to determine whether they should be approved for reimbursement in public health care systems [24]. Many HTA agencies require robust evidence demonstrating that a drug therapy is cost-effective, as well as clinically effective, to receive a positive reimbursement decision [5].…”
Section: Introductionmentioning
confidence: 99%